Challenges of Educational Management Information System: A Review - Adhikari, Narayan Prasad; Budhathoki, Jhupa Kumari (ILAM इलम, 2025)
This review aims to identify and analyze the challenges faced by educational institutions in implementing and utilizing educational management information system. The study is related to content analysis of relevant documents. Secondary data is used in this study. The EMIS is a system that uses new computer technology to make all the functions work together to give education leaders, decision makers, planners, and managers comprehensive, integrated, relevant, clear and timely data so they can carry out their duties effectively and meet the goals. By giving those needed the right information at the right time to make the best decisions, plan, and monitor in the organization's best interest. According to the study's findings, there are challenges such as disparities in knowledge and skill between those performing various system functions, a weak organizational structure and legal framework, and a lack of hardware, software, internet connectivity, and electrical power, particularly in the most remote and school-level locations in the area. It is found that despite the system's poor data quality, it can be regarded as effective because it provides the information and education data that many stakeholders demand. Officials at various levels are encouraged to prioritize and manage existing problems effectively, as most difficulties can be resolved with proper attention. Additionally, further research is recommended to develop appropriate solutions and strengthen the overall system.